Dark Web Investigation - Akhgar, Babak; Gercke, Marco; Vrochidis, Stefanos; Gibson, Helen (Security Informatics and Law Enforcement, 2021)
Part 1. Foundations -- Chapter 1. Understanding the Dark Web -- Chapter 2. Using the Dark Web -- Chapter 3. Terrorist activities in the Dark and the Surface Web -- Chapter 4. Dark Web Markets -- Chapter 5. TENSOR: A solution to dark web investigations -- Part 2. Legal and ethical considerations -- Chapter 6. Ethical and Societal Issues of automated Dark Web Investigation - Part 1 -- Chapter 7. Ethical and Societal Issues of automated Dark Web Investigation - Part 2 -- Chapter 8. Ethical and Societal Issues of automated Dark Web Investigation - Part 3 -- Chapter 9. Ethical and Societal Issues of automated Dark Web Investigation - Part 4 -- Chapter 10. Ethical and Societal Issues of automated Dark Web Investigation - Part 5 -- Part 3. Case studies -- Chapter 11. Case studies: Darkweb markets -- Chapter 12. Case studies: Child sexual exploitation -- Chapter 13. Case study: Match fixing on the Dark Web.